Ancient City, Universal Growth? Exploring Urban Expansion and Economic Development on Rome's Eastern Periphery - Mandich, Matthew J. (Frontiers in Digital Humanities, 2019)
This article investigates the urban expansion and economic development of ancient Rome through the application of models and theories originally designed for the study of contemporary cities. While the growth of ancient settlements is often difficult to track and analyze, archaeologically observable changes in land use can be read and interpreted as a function of broader economic oscillations over the longue durée. By re-examining the available archaeological and textual evidence pertaining to land use change on Rome’s eastern periphery this article demonstrates how the frameworks selected can be successfully appropriated via a narration of Rome’s urban transformations from the mid-Republic to the later Imperial period. The ultimate goal is to determine if the patterns of urban expansion identified in modern cities also existed in ancient Rome. The findings provided have the potential to produce rich insights on the dynamics of urban and economic growth across time and geographies, thereby opening the door for new and further studies.